Aluno-autor: a aprendizagem da leitura e escrita a partir de narrativas de mistério - Desirê Adrienne Oliveira Gonçalves (2018)
It is known that the teaching of reading and writing has been changing and being modeled according to the society we are part of, a globalized society, in which the students are seduced by technology and abandon reading. It thus makes the Portuguese language teachers work more difficult. It is searched for a new perspective to the teaching of reading and writing through what is called as literacy, in which the acts of reading and writing receive a new look from the students point of view. The research question was: how could the work of reading and writing be more efficient? The main objective is to propose different activities to motivate students to read and write. So, the idea was to develop workshops with thriller or mystery themed short stories for 7th grade students. The developed activities are based on the dialogic and responsive perspective of language. For that, readings were made to compose the theoretical basis on the theories of reading, theory of the short story, and literary literacy. Authors such as Todorov, Nádia Gotlib Batella, Antônio Cândido, Bordini, Cadermatori, Cotárzar, Cosson contributed in a unique way to give life to the idea of working with reading and writing using short stories. The conclusion is that we can work with literacy through playful activities, instead of simply filling book reports. Reading should lead to writing, an activity that is effective when the student makes sense of what he produces, when there is an answer for what was produced, when the dialogic relation actually takes place